(untitled) (Bangladesh Journal of Scientific Research, 2014)
Utilizing the 2007 BDHS data, this study examined the differential effect of decisionmaking power index on the use of contraception across different age cohorts of women. The findings indicated more pronounced impact of womens decision making power to increase contraception use aged above 25 than below 25 aged women. This implies more needs of promoting decision making power among the younger women (below 25) than the older women (above 25) for the betterment of family planning. However, decision making power did not show significant influence on decision of stopping womens childbearing in any of the younger and older women cohorts. DOI: http://dx.doi.org/10.3329/bjsr.v26i1-2.20232 Bangladesh J. Sci. Res. 26(1-2): 61-73, December-2013